INTEGRATING ETHNOMATHEMATICS INTO SECONDARY SCHOOL MATHEMATICS CURRICULUM FOR EFFECTIVE ARTISAN CREATIVE SKILL DEVELOPMENT - Ogunkunle, R. Abiodun; George, Nchelem R. (European Scientific Journal, ESJ, 2015)
This study employed a quasi experimental research design to investigate the effects of integrating ethnomathematics into secondary school mathematics curriculum for effective artisan creative skill development in Abia State, Nigeria. This study presented two experimental groups and one control group. Experimental group 1 was taught (raffia weaving) and experimental group 2 (pottery) by integrating ethnomathematics teaching approach into the conventional teaching approach via demonstration and discussion respectively. The control group was taught (traditional building) without integrating ethnomathematics teaching approach. Two research questions and two hypotheses guided the study. The population for this study was 407 Junior Secondary two students in all the public junior secondary schools in Isiala Ngwa North Local Government Area of Abia State. A simple random sampling technique was used to select 117 JS2 students. The instrument used for data collection was Artisan Skill Creativity Ability Test (ASCAT). The instrument was validated and the reliability index for ASCAT was 0.81. Mean, Standard Deviation and Mean Gain were used to answer the research questions while the Analysis of Covariance was used to test the hypotheses at .05 alpha level. The findings revealed that students taught by integrating ethnomathematics instructional approach via practical had the greatest mean gain in the acquisition of creative skills. There was a significant difference in the creative skills acquired by students for artisan skills development when taught using EIA and CIA. It was recommended among others that mathematics teachers should practically integrate ethnomathematics instructional approach to develop artisan creative skill in students.